Escola de educação infantil: saberes profissionais de professores e gestores - Parra, Andressa Carolina Scandelai [UNESP]; Pavaneli, Camila Fernanda Dias [UNESP; Nono, Maévi Anabel [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The present study aimed to investigate Childhood Education Professionals of knowledge have to respect the laws and documents published in Brazil from a 1980 aimed at this stage of basic education. It’s understood by both Professional Teachers the directors who work in day care centers and preschools. It’s a qualitative nature study was developed in period 2013-2014. Subjects of the research are 6 teachers and 3 directors who worked in nurseries and preschools seven municipalities and attended course "Knowledge Dissemination", via platform TelEduc. This analyzed were from the analysis focuses established with base Research Objectives. So, the objective: 1) knowledge of Early Childhood Professionals About Legislation, 2) knowledge of Early Childhood Professionals About Documents, 3) acquisition of sources of knowledge of Early Childhood Professionals About laws and documents and 4) such interference knowledge in Constitution of the identities of Early Childhood Professionals and ITS practices. The main results obtained suggest that the subjects have knowledge About laws and documents relating to Early Childhood Education published the last three decades in Brazil, BUT WITH some Important gaps in knowledge Taís as What can interfere with practices que develop with the Young Child and YOUR professional identity construction Like this stage of basic education. It is hoped through this research, provide subsidies for a Early Childhood Professional Training Policy Making.

Por meio desta pesquisa objetivou-se investigar saberes que profissionais de Educação Infantil possuem a respeito das leis e documentos publicados no Brasil, desde a década de 1980, voltados para essa etapa da Educação Básica. Entende-se por profissionais tanto professores(as) quanto gestores(as) que trabalham em creches e pré-escolas. Trata-se de um estudo de natureza qualitativa que foi desenvolvido no período 2013-2014. Os sujeitos da pesquisa foram 6 professores(as) e 3 gestoras que atuavam em creches e pré-escolas de 7 municípios brasileiros e que frequentaram curso de “Difusão de Conhecimento”, via Plataforma TelEduc, no qual os dados foram coletados. Os dados foram analisados a partir de focos de análise estabelecidos com base nos objetivos da pesquisa. Assim, os focos foram: 1) saberes dos profissionais de Educação Infantil sobre legislação, 2) saberes dos profissionais de Educação Infantil sobre documentos, 3) fontes de aquisição dos saberes dos profissionais de Educação Infantil sobre leis e documentos e 4) interferência de tais saberes na constituição das identidades dos profissionais de Educação Infantil e em suas práticas. Os principais resultados obtidos sugerem que os sujeitos possuem saberes sobre leis e documentos relativos a Educação Infantil publicados nas últimas três décadas no Brasil, mas com algumas lacunas importantes em tais saberes, as quais podem interferir nas práticas que desenvolvem com as crianças pequenas e na construção de sua identidade como profissional desta etapa da Educação Básica. Espera-se, por meio desta pesquisa, oferecer subsídios para a formulação de políticas de formação de profissionais de Educação Infantil.
Keywords: Early childhood education; Knowledge professionals; Law; Educação infantil; Saberes profissionais; Legislação